Bagaimana kesadaran masyarakat Desa BDLK Jombang terhadap hak anak?: Studi kualitatif deskriptif - Putri Varadhiva A.K; Cici Indah Cahyawati; Bima Reksi Kurniawan; Tatik Meiyuntariningsih; IGAA Noviekayati; Hikmah Husniyah Farhanindya (INNER: Journal of Psychological Research, 2023)
Children are a wonderful gift from the almighty god, whose dignity and dignity we must always keep and preserve as we must. The future of the nation rests on the child as well. Crimes against children at very advanced ages and young are also increasing each year. In addition to government regulations and programs, there is also the need for community, family, and childcare. Hence, the study was done to give the public insight into the rights of both legal and psychological children. The method used in this study is descriptive qualitative research. Using observational data collection techniques and interviews. This study suggests that it is important for society to know what rights children should have in order to prevent and correct those rights Keywords: Public Consciousness, Childs Right.